Black iconography and colonial (re)production at the ICC : (in)dependence cha cha cha? - Wanjiru, Mwangi (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book explores the reproduction of colonialism at the International Criminal Court (ICC), and examines International criminal law (ICL) vs the Black body through an immersive format of Art, Music, Poetry, and Architecture and post-colonial/critical race theory lens. Taking a multi-disciplinary approach, the book interrogates the operationalization of the Rome statute to detail a Eurocentric hegemony at the core of ICL. It explores how colonialism and slavery have come to shape ICL, exposing the perpetuation of the colonial and warns that it heralds ominous contemporary and future implications for Africa. As currently envisaged and acted out at the ICC, this law is founded on deceptive and colonial ideas of 'what is wrong' in/with the world. The book finds that the contemporary ICL regime is founded on white supremacy that corrupts the law's interaction with the African. The African is but a unit utilised by the global elite to exploit and extract. From time to time, these alliances disintegrate with ICL becoming a retaliatory tool of choice. What is at stake, is power, not justice. This power is hierarchical with Eurocentrism at the top throughout modern history. Colonialism is seen not to have ended but to have regerminated through the foundation of the 'independent' African state. The ICC reproduces the colonial by use of European law, and ultimately the over representation of the black accused. To conclude, the book provides a liberated African forum that can address conflicts in the content, with a call for the end of the ICC's involvement in Africa. The demand is made for an African Court that utilises non-colonising African norms which are uniquely suited to address local conflicts. Multidisciplinary in nature, this book will be of great interest to students and scholars of International Criminal Law, Criminal Justice, Human Rights Law, African Studies, Global Social Justice, Sociology, Anthropology, Postcolonial Studies, and Philosophy"--
OCLC-licensed vendor bibliographic record.
Keywords: International Criminal Court; Discrimination in criminal justice administration; Intercultural communication; Eurocentrism; Racism; Stereotypes (Social psychology); LAW / Criminal Law / General